Influence of Dietary Capsaicin on Redox Status in Red Blood Cells During Human Aging - Prabhanshu Kumar; Subhash Chand; Pranjal Chandra; Pawan Kumar Maurya (Tabriz University of Medical Sciences, 2015)
Purpose: Capsaicin (8-methyl-N-vanillyl-6-nonenamide) is a major pungent compound found in hot peppers of the plant genus Capsicum. In vitro effects of dietary capsaicin on redox status in red blood cells during human aging have been explored. Methods: Total antioxidant potential of capsaicin was evaluated using Ferric reducing ability of plasma (FRAP) assay. GSH was measured as per standard protocol. The in vitro effect of capsaicin was evaluated by incubation of the cells in the assay medium with 10-5M capsaicin (final concentration) for 60 min at 37°C. Results: Treatment with capsaicin (10-5M) caused a significant (p < 0.01) increase in GSH level in all age groups. Reduced glutathione (GSH) / Oxidized glutathione (GSSG) ratio measures the redox status of the red blood cell. Significant increase in GSH level due to capsaicin, shift the GSH/GSSG ratio, thus alters the redox status of the cell. Conclusion: The results conclusively prove the efficacy of the antioxidant property of capsaicin and its role in modulating the redox status of red blood cells. This evidence suggests that dietary factors that act as antioxidants to increase GSH level may contribute to a protective effect against age related diseases. This antioxidant effect may, in part, explain the high consumption of capsicum in certain regions of the world.